Counterradicalism in Efforts to Prevent Radicalism in Rechtsbewutstzijn-Based Universities - Puspitosari, Hervina Puspitosari; Yana Indawati; Wiwin Yulianingsih (International Journal of Educational Research & Social Sciences, 2021)
The target of the spread of radical terrorism that has infiltrated the university environment needs to be prevented and become a common concern, especially university leaders. The development of the radical flow of terrorism in universities can endanger the unity of the state because universities are a place for education candidates for intellectuals, entrepreneurs, bureaucrats, technocrats, and professionals. Counter-radicalism is an effort to prevent the entry of the seeds of radicalism in the transformation of terrorism in universities. Prevention and control efforts can be carried out through a soft education approach by instilling the spirit of nationalism and defending the country to students and academics in the Higher Education environment. Rechtsbewustzijn is closely related to legal compliance and the effectiveness of the law, so it is hoped that the values ​​of legal awareness that are built strongly in the Higher Education environment will be successful in supporting counter-radicalism programs in preventing radicalism in Higher Education. All components in Higher Education in obeying the law are not a compulsion but because the law is by the values ​​that exist in society and by the needs of the Higher Education environment which is a safe and comfortable place to study.